Care providers’ knowledge and practice of malaria control measures in pregnancy in Ibadan, South west Nigeria (2012)
Background: Effective prevention and control of malaria during pregnancy include prompt and effective case management of malaria combined with prevention of infection by the use of insecticide-treated nets and intermittent preventive treatment in pregnancy (IPTp). Care givers knowledge and practice of malaria control is pivotal to effective implementation of these guidelines. The objective of this study was to determine the awareness of care providers in facilities offering maternity services in Ibadan of the National Malaria Treatment Guideline and Policy in Nigeria. The study also aimed to describe the prescription practice, for malaria chemoprophylaxis and case management in pregnancy, by these care providers. Materials and method: The study was a cross-sectional survey of the; lead care givers in all registered hospitals and maternity centres in Ibadan over one year (April 2008 to April 2009), using structured questionnaires. The list of the one hundred and thirty-two (132) registered centres was obtained from the State Ministry of Health. The lead care givers provided information, on their awareness of the new government policy and antimalarials believed to be effective and prescribed for malaria prevention and case management in pregnancy. Results: Over two thirds (84.2%) of the facilities were operated by either Medical Officers with only basic medical training or by Nurses/Mid wives. The modes of prevention most commonly reported as being effective were the use of insecticide spray, window nets and ITN. The drugs most commonly prescribed for chemoprophylaxis were sulphadoxine-pyrimethamine (SP) (65.2%), Proguanil (45.5%) and pyrimethamine (42.4%). The drugs most commonly prescribed for case management were ACIfe (66.7%), amodiaquine (59.8%) and artemether (47.7%). Quite a number of respondents were unsure of the frequency (81.8%) and timing (56.5%) of administration of sulphadoxine- pyrimethamine for prophylaxis. Conclusion: This study demonstrates awareness but lack of in-depth knowledge of control measures. Also, there is poor use of the recommended agent for IPT. The factors militating against the use of these preventive measures need to be urgently explored and addressed.